2019
DOI: 10.1074/jbc.ra118.006917
|View full text |Cite
|
Sign up to set email alerts
|

Global biochemical and structural analysis of the type IV pilus from the Gram-positive bacterium Streptococcus sanguinis

Abstract: Type IV pili (Tfp) are functionally versatile filaments, widespread in prokaryotes, that belong to a large class of filamentous nanomachines known as type IV filaments (Tff). Although Tfp have been extensively studied in several Gram-negative pathogens where they function as key virulence factors, many aspects of their biology remain poorly understood. Here, we performed a global biochemical and structural analysis of Tfp in a recently emerged Gram-positive model, Streptococcus sanguinis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(97 citation statements)
references
References 55 publications
1
85
0
Order By: Relevance
“…Prepilins (major and minor) are first translocated via the SRP‐Sec pathway across the cytoplasmic membrane (CM) (Arts et al , ; Francetic et al , ), where they remain initially as bitopic proteins with their α1N behaving as a transmembrane domain. Their leader peptide is then processed after the conserved Gly by the prepilin peptidase (Aly et al , ), which also methylates the first residue of mature pilins as confirmed in S. sanguinis (Berry et al , ). It is unclear at this stage, if the minor pilins are assembled first and cap the filaments as proposed for other Tff (Korotkov and Hol, ).…”
Section: Tfp Assembly: Lessons From Monoderm Bacteriamentioning
confidence: 97%
See 4 more Smart Citations
“…Prepilins (major and minor) are first translocated via the SRP‐Sec pathway across the cytoplasmic membrane (CM) (Arts et al , ; Francetic et al , ), where they remain initially as bitopic proteins with their α1N behaving as a transmembrane domain. Their leader peptide is then processed after the conserved Gly by the prepilin peptidase (Aly et al , ), which also methylates the first residue of mature pilins as confirmed in S. sanguinis (Berry et al , ). It is unclear at this stage, if the minor pilins are assembled first and cap the filaments as proposed for other Tff (Korotkov and Hol, ).…”
Section: Tfp Assembly: Lessons From Monoderm Bacteriamentioning
confidence: 97%
“…B) and 3D structure (Fig. C) (Berry et al , ). It remains to be seen whether such a heteropolymeric structure might be a more general property of Tfp in monoderms, which awaits purification and biochemical characterisation of filaments in other species.…”
Section: Monoderm Bacteria Produce Tfpmentioning
confidence: 98%
See 3 more Smart Citations